2011
DOI: 10.1590/s1516-35982011000300023
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative characteristics of carcass and meat quality of ¾ Boer + ¼ Saanen and Saanen goat kids fed diets with dry yeast

Abstract: -Twenty-seven carcasses of non-castrated confined goat kids, (18 ¾ Boer + ¼ Saanen and nine Saanen) with slaughtered weight of 30.1 ± 0.27 kg were used to evaluate quantitative characteristics of the carcass and qualitative characteristics of the loin and shoulder. The animals were distributed in a completely randomized design in a 2 × 3 factorial arrangement (breed group × diet). The diets consisted of inclusion of dry yeast, as follows: soybean meal, soybean meal + dried yeast or dried yeast. The other ingre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
5
4
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 20 publications
5
5
4
2
Order By: Relevance
“…It is in agreement with Freitas et al (2011), who found influence of feeding systems on the muscle yield of ¾ Boer x Saanen and Saanen goats, slaughtered with an average weight of 30 kg, obtaining values of 708.9; 735.8 and 695.2 g kg -1 for the three feeding systems used.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…It is in agreement with Freitas et al (2011), who found influence of feeding systems on the muscle yield of ¾ Boer x Saanen and Saanen goats, slaughtered with an average weight of 30 kg, obtaining values of 708.9; 735.8 and 695.2 g kg -1 for the three feeding systems used.…”
Section: Resultssupporting
confidence: 91%
“…The leg compactness index (Table 4) was higher in 3/4 and 7/8 Boer x Alpine breed groups, which is in accordance with Freitas et al (2011), who observed the influence of breed group in the leg compactness index, in which 3/4 Boer x Saanen kids showed better results than the Saanen breed group. The feeding system did not influence the leg compactness index, which is in agreement with Grande et al (2003), who found no influence of different feeding systems in the leg compactness index in kids.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations